PS 11-45 A PROSPECTIVE STUDY OF LEUKOCYTE DNA COPY NUMBER AND NEW ONSET METABOLIC SYNDROME: THE ARIRANG STUDY. (September 2016) - Kim, Jang Young; Son, Jung Woo; Lee, Jun Won; Youn, Young Jin; Ahn, MIn Su; Yoon, Junghan; Sohn, Joon Hyung; Koh, Sang Baek; Park, Kyu Sang; Ahn, Song Vogue; Yoo, Byung Su; Lee, Seung Hwan
Abstract : Objective: Metabolic syndrome (MetS) is characterized by a group of defects of metabolic origin which are possibly involved in mitochondrial DNA (mtDNA) alteration of mtDNA content, but there was no prospective study of the predictive value of leukocyte mtDNA copy number to identify individuals at high risk of new-onset metabolic syndrome. We investigated whether leukocyte mtDNA copy number predicts the metabolic syndrome in a population-based longitudinal study. Design and Method: A prospective cohort study was conducted of random sample 221 adults aged 40–70 years without metabolic syndrome examined in 2005–2008 (baseline) and 2008–2011 (follow-up). Baseline mtDNA copy number of leukocytes was measured using quantitative polymerase chain reaction. Results: During an average of 2.8 years of follow-up, 82 (36.6%) developed new onset metabolic syndrome. The mean mtDNA copy number in metabolic syndrome was significantly lower than that in non-metabolic syndrome (113.79 ± 51.31 vs. 132.79 ± 51.31/cell, p < 0.001) In multivariable-adjusted models, the odds ratio for new onset metabolic syndrome comparing the highest with the lowest quartiles of mtDNA copy number was 0.34 (95% CI 0.13–0.91). The corresponding odds ratios for high waist circumference, low HDL cholesterol, high triglycerides, high blood pressure, and high blood glucose were 0.33(0.10–1.06), 0.26 (0.10–0.68), 0.40 (0.17–0.94), 0.70 (0.31–1.57), and 0.70 (0.31–1.61), respectively. Conclusions: Increased leukocyte mtDNA copy number is an independent protective factor for new onset metabolic syndrome and its components. Leukocyte mtDNA copy number might be a novel biomarker involved in the bioenergetics change of mitochondria.